Musealising hope: reflections on the saga of an artistic installation of human solidarity (Cadernos de Sociomuseologia, 2010)
“Musealising hope” reflects on the trials and tribulations of an installation designed as a tribute to the struggle for survival of African peoples who dare make the long trek to Europe by sea. Its accomplishment involved a number of players whose conduct and reactions to events bear witness to the manner in which artists, the media, heads of cultural institutions, museologists, welfare institutions, and politicians cope with the phenomenon of immigration and with our present-day multicultural societies. In turn, this artistic endeavour and its symbolic signification highlight the changes which art and culture have undergone over the past few years and the kind of transformation which new inter-ethnic communities have brought to bear on concepts such as national heritage, identity or memory.